2021
DOI: 10.1371/journal.pgen.1009383
|View full text |Cite
|
Sign up to set email alerts
|

TOR functions as a molecular switch connecting an iron cue with host innate defense against bacterial infection

Abstract: As both host and pathogen require iron for survival, iron is an important regulator of host-pathogen interactions. However, the molecular mechanism by which how the availability of iron modulates host innate immunity against bacterial infections remains largely unknown. Using the metazoan Caenorhabditis elegans as a model, we demonstrate that infection with a pathogenic bacterium Salmonella enterica serovar Typhimurium induces autophagy by inactivating the target of rapamycin (TOR). Although the transcripts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Previous findings demonstrated that the Tor kinase could function as a molecular switch connecting an iron cue to defend against pathogen infection in C. elegans [56] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings demonstrated that the Tor kinase could function as a molecular switch connecting an iron cue to defend against pathogen infection in C. elegans [56] .…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism underlying SKN-1-mediated innate immunity remains unclear. Previously, we and others have demonstrated that autophagy plays an important role in C. elegans defense against a variety of pathogenic bacteria by repairing organismal insults [ 15 , 20 , 48 ]. SKN-1 up-regulates a set of autophagic genes in the germline-deficient glp-1 (e2141ts) mutants [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the mechanistic target of rapamycin (mTOR) pathway has been described as a regulator of autophagy and ferritin activation (Ma et al, 2021 ). The correlation between these processes was observed in C. elegans following external iron supply and simultaneous infection with pathogens.…”
Section: Biological Roles Of Ferritinsmentioning
confidence: 99%
“…FTN-1 and FTN-2 were demonstrated to be important for defense against pathogen infection, but only when worms were exposed to exogenous iron. In the described conditions, ferritin was responsible for limiting the accessibility of iron used by pathogens for growth (Ma et al, 2021 ).…”
Section: Biological Roles Of Ferritinsmentioning
confidence: 99%
See 1 more Smart Citation